2015
DOI: 10.1177/1099800415585157
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal and Infant Testosterone and Cortisol Levels With Maternal Depressive Symptoms and Infant Socioemotional Problems

Abstract: This study examined the associations of testosterone and cortisol levels with maternal depressive symptoms and infant socioemotional (SE) problems that are influenced by infant gender. A total of 62 mothers and their very-low-birth weight (VLBW) infants were recruited from a neonatal intensive care unit at a tertiary medical center in the southeast United States. Data were collected at three time points (before 40 weeks’ postmenstrual age [PMA] and at 3 months and 6 months of age corrected for prematurity). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These data suggest that a portion of consumers may benefit from the use of graphs (e.g., bar and line) to understand certain biobehavioral findings. In a rare occurrence in the present study sample, Cho, Su, Phillips, and Holditch-Davis (2016, Figure 3) presented the same Center for Epidemiological Studies for Depression Scale data as both a line graph and a table, arguably attending to the variety of consumer characteristics. However, authors, in general, will want to present data as a table or graph and not in both visual forms.…”
Section: Discussionmentioning
confidence: 64%
“…These data suggest that a portion of consumers may benefit from the use of graphs (e.g., bar and line) to understand certain biobehavioral findings. In a rare occurrence in the present study sample, Cho, Su, Phillips, and Holditch-Davis (2016, Figure 3) presented the same Center for Epidemiological Studies for Depression Scale data as both a line graph and a table, arguably attending to the variety of consumer characteristics. However, authors, in general, will want to present data as a table or graph and not in both visual forms.…”
Section: Discussionmentioning
confidence: 64%
“…We have used theories of gender differences to examine the associations of maternal and infant salivary testosterone and cortisol levels with neonatal health and growth; as well as maternal depressive symptoms and infant socioemotional problems (Cho et al, 2012; Cho & Holditch-Davis, 2014; Cho, Su, Phillips, & Holditch-Davis, 2016). We also reported that positive mother-infant interactions can be an influential factor affecting infant development (Cho, Su, Phillips, & Holditch-Davis, 2015).…”
Section: Methodsmentioning
confidence: 99%